2017
DOI: 10.1063/1.4979346
|View full text |Cite
|
Sign up to set email alerts
|

Shock and spall behaviors of a high specific strength steel: Effects of impact stress and microstructure

Abstract: A series of plate-impact experiments were conducted to investigate the influences of impact stress and microstructure on the shock and spall behaviors of a high specific strength steel (HSSS). The HSSS shows a strong positive strain rate sensitivity on the yield strength. With increasing impact stress up to about 6 GPa, the spall strength is found to decrease significantly and then levels off with further increasing impact stress. This trend is proposed to be attributed to the accumulation damage within the ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 68 publications
0
16
0
Order By: Relevance
“…The details for the preparation of the HSSS can be found in our previous papers [25,26]. The hot-rolled plates with a thickness of 7.3 mm were cold rolled into a final thickness of 1.5 mm, and then were annealed at 1173 K for 15 min followed immediately by water quenching.…”
Section: Materials and Experimental Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…The details for the preparation of the HSSS can be found in our previous papers [25,26]. The hot-rolled plates with a thickness of 7.3 mm were cold rolled into a final thickness of 1.5 mm, and then were annealed at 1173 K for 15 min followed immediately by water quenching.…”
Section: Materials and Experimental Proceduresmentioning
confidence: 99%
“…This HSSS shows excellent combination of specific strength and elongation when compared to the other low-density metals and alloys. In our previous research [25,26], it has been shown that this UFG HSSS should be better understood as a dual-phase microstructure since the B2 phase is deformable. Thus, the stress/strain partitioning between the constituent phases and the back-stress-induced strain hardening should play important roles during the plastic deformation for this HSSS.…”
Section: Introductionmentioning
confidence: 95%
“…Kim et al [20] has attributed the outstanding mechanical properties of this HSSS to the precipitation strengthening by the brittle B2 intermetallic compound. In our previous work [21,22], the stress/strain partitioning between the constituent phases and the back-stress-induced strain hardening have been found to play an important role during the plastic deformation for this HSSS, since the B2 phase was found to be deformable.…”
Section: Introductionmentioning
confidence: 75%
“…%) was produced using arc melting under protection of pure argon atmosphere, and the detailed procedures for preparing the hot-rolled (HR) strips can be found in our previous papers [21,22]. The HR strips with a thickness of 3.9 mm were annealed at 1000 • C for 1 h first, and then were cold rolled (CR) into a final thickness of 1.3 mm with a thickness reduction of 66%.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation